Anemia Is a Predictor of Withdrawal from Peritoneal Dialysis in Stable Peritoneal Dialysis Patients - Kenta Torigoe; Emiko Otsuka; Kiyokazu Tsuji; Ayuko Yamashita; Mineaki Kitamura; Takahiro Takazono; Noriho Sakamoto; Kumiko Muta; Hiroshi Mukae; Tomoya Nishino (Kidney and Dialysis)
Introduction: The association between anemia and peritoneal dialysis (PD) withdrawal in patients with stable PD remains poorly established. Herein, we investigated the relationship between anemia and PD withdrawal in patients with stable PD. Materials and Methods: We included 43 patients undergoing PD for at least 6 months between October 2011 and December 2022. Patients were categorized based on their hemoglobin (Hb) levels at the time of their first peritoneal equilibration test (PET) during the study period as follows: Hb ≥ 11 g/dL and Hb < 11 g/dL. The PD withdrawal rates were compared between these groups. Patients were followed up until death or 31 July 2023. Results: During the follow-up, 36 patients discontinued treatment. Patients with Hb < 11 g/dL had a significantly higher PD withdrawal rate than those with Hb ≥ 11 g/dL. Cox proportional hazards analysis identified Hb level as a risk factor for PD withdrawal. Furthermore, Hb levels negatively correlated with the annual decline in urine volume. Conclusions: Our findings suggest anemia as a predictor of PD withdrawal in patients with stable PD. The negative correlation between Hb levels and the annual decline in urine volume implies that anemia may contribute to PD withdrawal via the deterioration of residual renal function.